Assessment of the prevalence of kyphosis disorders in students - Leila Ghorbani; Abdol Hamid Daneshjoo; Alibagher Nazarian (Vesnu Publications, 2010)
Introduction: The aim of this study was to assess the prevalence of kyphosis disorders in students. Materials and Methods: Five hundred and two students in three levels including primary (99 girls, 99 boys) guidance (47 girls, 57 boys), and high schools (100 girls, 100 boys) participated in this study. Frontal Cobb angle was measured by flexi curve ruler. Data were analyzed by chi square. After collecting the data, subjects were classified in 4 categories includeing flat back, normal, kyphosis, and hyperkyphosis. Results: In all 256 boys, 2% had flat back (2%), normal (76.6%), kyphosis (21.4%) and in 256 girls (4.5%), showed flat Bach, flat back normal (80%), kyphosis (15%), but there were significant differences between their disorders (P > 0.05). There was significant difference between boy and girls in elementary school (P < 0.05). In guidance and high school boy and girls, there were significant differences between their spinal deformities (flat back, normal and kyphosis). Conclusion: We concluded that reducing improper habits and familiarized the children with proper way of carrying her or his bags and performing proper activities such as sitting, sleeping and also participated in regular training, can reduces the risk of spinal deformities. Keywords: Kyphosis disorders, Students, Cobb angle.